The Effect of Behaviorally Anchored Rating Scale (BARS) Implementation on Quality of Work Life Improvement with Emotional Exhaustion as a Mediating Variable among Nurses at Bhayangkara Clinic - idyasanthi, Komang Ayu Sri W; Rahim, Agus Hadian; Rinawati, Rinawati (Business Management, 2025)
This study aimed to analyze the effect of Applying Behaviorally Anchored Rating Scale (BARS), Quality of Work Life (QWL), and Emotional Exhaustion on employees, as well as to test whether Emotional Exhaustion mediates the relationship between BARS and QWL. This study employs a quantitative approach, utilizing regression analysis to examine the relationship between these variables. The results showed that BARS had a significant negative effect on Emotional Exhaustion, although the effect was relatively small. Quality of Work Life was also found to have a significant negative effect on Emotional Exhaustion, with a stronger effect than BARS. In addition, the results of this study confirm that Emotional Exhaustion mediates the relationship between BARS and Quality of Work Life, suggesting that increased BARS can improve Quality of Work Life through a reduction in the level of Emotional Exhaustion. This research makes a significant contribution to human resource management by designing policies that enhance employee well-being, such as implementing a clear performance appraisal system and improving the quality of the work environment that supports emotional well-being.